DYNAMIC ARCHITECTURE AS A NEW STEP OF PUBLIC DEVELOPMENT SPACES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main advantages of such facilities should be the following qualities: versatility, compactness, rationality, availability, autonomy and flexibility in operation. Modern public spaces are more and more expressive architectural complexes intended for various types of cultural activities and located within the same recreational area.